Dataset of electrophysiological patch-clamp recordings of the effect of the compounds deltamethrin, ATx-II and β4-peptide on human cardiac Nav1.5 sodium channel gating properties - Thull, Sarah; Neacsu, Cristian; O'Reilly, Andrias O.; Bothe, Stefanie; Hausmann, Ralf; Huth, Tobias; Meents, Jannis; Lampert, Angelika (Data in Brief, 2020)
This article describes the effect of the pyrethroid insecticide deltamethrin on the cardiac voltage-gated sodium channel Nav1.5. Two concentrations of deltamethrin were used and the effects were compared with those of the sea anemone toxin ATx-II and β4-peptide, which is the C-terminus of the Nav channel β-subunit. Activation, fast inactivation, deactivation, persistent currents and resurgent currents of Nav1.5 channels were assessed in the presence of these compounds. The data display not only the effect of separately applied compounds on Nav1.5 channels but also investigates how combinations of these substances affect Nav1.5 channel gating properties. The dataset presented in this article is related to the research article “Mechanism underlying hooked resurgent-like tail currents induced by an insecticide in human cardiac Nav1.5″ (Sarah Thull, Cristian Neacsu, Andrias O. O'Reilly, Stefanie Bothe, Ralf Hausmann, Tobias Huth, Jannis Meents, Angelika Lampert, doi: 10.1016/j.taap.2020.11501), that investigates the effect of the pyrethroid insecticide deltamethrin on Nav channel gating properties and explains the mechanism underlying hooked, resurgent-like tail currents induced by deltamethrin in Nav1.5 channels.
CRIS-Team Scopus Importer:2020-07-17
Keywords: ATx-II; Deltamethrin; Human Nav1.5; Persistent current; Resurgent current; Sodium channel gating states; Voltage-gated sodium channel; β4-peptide